Combining seasonal forecasts and artificial intelligence to improve agronomy at scale - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
We have used the approach developed by Dorado et al. (2019) (see link provided) combined with seasonal forecasts (Esquivel et al., 2018) to produce a proof of concept where we combine seasonal forecasts and artificial intelligence prediction models for optimizing agronomic practices.